A randomized clinical trial of tailored interventions for health promotion and recidivism reduction among homeless parolees: outcomes and cost analysis - Nyamathi, Adeline M. (J Exp Criminol, 2015)
OBJECTIVES: This study conducted a randomized controlled trial with 600 recently released homeless men exiting California jails and prisons. METHODS: The purpose of this study was to primarily ascertain how different levels of intensity in peer coaching and nurse-partnered intervention programs may impact reentry outcomes; specifically: (a) an intensive peer coach and nurse case managed (PC-NCM) program; (b) an intermediate peer coaching (PC) program with brief nurse counseling; and (c) the usual care (UC) program involving limited peer coaching and brief nurse counseling. Secondary outcomes evaluated the operational cost of each program. RESULTS: When compared to baseline, all three groups made progress on key health-related outcomes during the 12-month intervention period; further, 84.5 % of all participants eligible for hepatitis A/B vaccination completed their vaccine series. The results of the detailed operational cost analysis suggest the least costly approach (i.e., UC), which accounted for only 2.11 % of the total project expenditure, was as effective in achieving comparable outcomes for this parolee population as the PC-NCM and PC approaches, which accounted for 53.98 % and 43.91 %, respectively, of the project budget. CONCLUSIONS: In this study, all three intervention strategies were found to be comparable in achieving a high rate of vaccine completion, which over time will likely produce tremendous savings to the public health system.